2021
DOI: 10.1515/htmp-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of physicochemical properties of quick lime at converter-smelting temperature

Abstract: The volume stability caused by the hydration of f-CaO is one of the main obstacles to the comprehensive utilization of steel-making slag. In view of the f-CaO produced by incomplete dissolution of lime, it is necessary to strengthen the dissolution behavior of lime in the converter process. The reactivity of lime determines the dissolution efficiency and is closely related to its microstructure. The experimental results show that the reactivity and porosity of quick lime decrease and the average diameter of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The reactions are shown in Equation (4)–(6). [ 12–16 ] CaO+(FeO)(CaOFeO)$$\text{CaO+} \left(\right. \text{FeO} \left.\right) \rightarrow \text{(CaO} \cdot \text{FeO)}$$CaO+(MgO)+(FeO)+(SiO2)3(CaMgFe)normalOSiO2$$\text{CaO+} \left(\right.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions are shown in Equation (4)–(6). [ 12–16 ] CaO+(FeO)(CaOFeO)$$\text{CaO+} \left(\right. \text{FeO} \left.\right) \rightarrow \text{(CaO} \cdot \text{FeO)}$$CaO+(MgO)+(FeO)+(SiO2)3(CaMgFe)normalOSiO2$$\text{CaO+} \left(\right.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction process is shown in Equation (7). [ 12–16 ] (3CaOMgO2SiO2)+CaO2(2CaOSiO2)+(MgO)$$\text{(3CaO} \cdot \text{MgO} \cdot \left(\text{2SiO}\right)_{2} \text{)+CaO} \rightarrow \text{2(2CaO} \cdot \left(\text{SiO}\right)_{2} \text{)+(MgO)}$$…”
Section: Discussionmentioning
confidence: 99%
“…However, the slag composition will be calculated based on the amount of flux melted. Many scholars have studied the dissolution behavior of lime in the converter melt pool [25][26][27][28]. Figure 4 shows the schematic diagram of the lime-melting process.…”
Section: Calculation Of Steel Slag Quantitymentioning
confidence: 99%
“…Pornchai et al proposed that the optimum condition for the calcination of eggshells is a treatment at 800°C for 1 h [22]. Higher calcination temperatures and prolonged calcination times decrease the surface area, pore size, and reactivities of the calcium oxide product [23][24][25][26]. However, research involving eggshell calcination has normally been conducted in lab-scale furnace with a small amount (0.5-10 g) of eggshells being used for each batch.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no studies involving the calcination of eggshells in an industrial-scale furnace have been reported before. The heating process of the furnace plays a significant role, since major rearrangements of the raw material microstructure occur which have a direct impact on the properties of the final product [24]. Thus, up-scaling to an industrial scale is crucial for assessing the optimum operating conditions, as it is similar to a commercial scale.…”
Section: Introductionmentioning
confidence: 99%